Epineurial Nerve Coaptation: A Biological Nonliving Training Model Using Gradually Thawed Cryopreserved Sciatic Nerves. Issue 7 (October 2018) - Safi, Ali-Farid; Safi, Sema; Timmer, Marco; Goldbrunner, Roland; Kauke, Martin
Abstract : Abstract: The authors present a novel biological nonliving epineurial nerve coaptation training model, which allows cost-efficient practicing on organic mammal nerves and offers an objective performance control on the basis of successful suturing and respecting the 3R model. Anatomic dissection of 40 rat cadavers was performed. Four residents without prior microneurosurgical experience were included. Each trainee performed 20 epineurial nerve coaptations. The number of successful sutures served as qualitative variable and operation time as a quantitative variable for efficiency control. The rate for successful sutures was 51.9% in the first half of trials and improved to 94.4% in the second half. Whereas, the trainees needed a mean time of 34 minutes for the first 10 coaptations, the last 10 coaptations were performed within 24.5 minutes. The authors' presented model is an easily accessible, low-cost microneurosurgical simulation model, allowing a realistic and instructive performance of epineurial nerve coaptation. Because cadaveric nerves are used, an approval of the local ethics committee is not needed. Furthermore, anatomic knowledge about the topography related to the harvest of the sciatic nerve of rats is provided in this study.